Peningkatan Hasil Belajar Ski Melalui Metode Problem Based Learning Dan Media Audio Visual - Santi Lian Nurfadila (Program Studi Pendidikan Agama Islam, 2022)
This study aims to improve learning outcomes of the SKI through Problem Based Learning methods and audio visual media. This research uses classroom action research with two cycles, and uses the Kemis and MC. Taggart model which consists of planning, implementation, observations, reflections. The research subjects are VIII MTs NU Ungaran with 36 students consisting of 18 girls and 18 boys. The results showed that there was an increase in learning outcomes in cycle 1 to cycle 2. It can be said that the usual Problem Based Learning methods and audio visual media can improve learning outcomes of the SKI.